# ln(2x+5)=ln(6x-1)

## Simple and best practice solution for ln(2x+5)=ln(6x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for ln(2x+5)=ln(6x-1) equation:

Simplifying
ln(2x + 5) = ln(6x + -1)
Reorder the terms:
ln(5 + 2x) = ln(6x + -1)
(5 * ln + 2x * ln) = ln(6x + -1)
(5ln + 2lnx) = ln(6x + -1)
Reorder the terms:
5ln + 2lnx = ln(-1 + 6x)
5ln + 2lnx = (-1 * ln + 6x * ln)
5ln + 2lnx = (-1ln + 6lnx)
Solving
5ln + 2lnx = -1ln + 6lnx
Solving for variable 'l'.
Move all terms containing l to the left, all other terms to the right.
Add 'ln' to each side of the equation.
5ln + ln + 2lnx = -1ln + ln + 6lnx
Combine like terms: 5ln + ln = 6ln
6ln + 2lnx = -1ln + ln + 6lnx
Combine like terms: -1ln + ln = 0
6ln + 2lnx = 0 + 6lnx
6ln + 2lnx = 6lnx
Add '-6lnx' to each side of the equation.
6ln + 2lnx + -6lnx = 6lnx + -6lnx
Combine like terms: 2lnx + -6lnx = -4lnx
6ln + -4lnx = 6lnx + -6lnx
Combine like terms: 6lnx + -6lnx = 0
6ln + -4lnx = 0
Factor out the Greatest Common Factor (GCF), '2ln'.
2ln(3 + -2x) = 0
Ignore the factor 2.
Subproblem 1Set the factor 'ln' equal to zero and attempt to solve:
Simplifying
ln = 0
Solving
ln = 0
Move all terms containing l to the left, all other terms to the right.
Simplifying
ln = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(3 + -2x)' equal to zero and attempt to solve:
Simplifying
3 + -2x = 0
Solving
3 + -2x = 0
Move all terms containing l to the left, all other terms to the right.
Add '-3' to each side of the equation.
3 + -3 + -2x = 0 + -3
Combine like terms: 3 + -3 = 0
0 + -2x = 0 + -3
-2x = 0 + -3
Combine like terms: 0 + -3 = -3
-2x = -3
Add '2x' to each side of the equation.
-2x + 2x = -3 + 2x
Combine like terms: -2x + 2x = 0
0 = -3 + 2x
Simplifying
0 = -3 + 2x
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`